2013
DOI: 10.1177/0739456x12468771
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Community Design and Crashes Involving Older Drivers and Pedestrians

Abstract: This study uses negative binomial regression models to understand how urban form may affect total and KSI (killed or seriously injured) crashes involving drivers and pedestrians aged seventy-five and older. Intersections, strip commercial establishments, big box stores, and arterial thoroughfares were associated with increases in crashes involving older motorists, while big box stores and arterials increased crashes for older pedestrians. Networks of lower-speed streets were associated with fewer crashes invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In addition to the preceding contributing factors, road network structures have been identified as important in determining traffic safety, especially for pedestrians (Marshall and Garrick, 2010b;Rifaat et al, 2011Rifaat et al, , 2012Wei and Lovegrove, 2012;Dumbaugh and Zhang, 2013;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the preceding contributing factors, road network structures have been identified as important in determining traffic safety, especially for pedestrians (Marshall and Garrick, 2010b;Rifaat et al, 2011Rifaat et al, , 2012Wei and Lovegrove, 2012;Dumbaugh and Zhang, 2013;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative framework relating roadside design to traffic safety, potentially better suited to urban settings, posits that drivers are more aware of potential hazards and engage in less risky behavior when their environment is more constrained and offers less design consistency (Figure 2b) (3)(4)(5)(6)(7). It takes advantage of driver agency to respond to environmental conditions with slower speeds, improving a driver's capacity to react to unpredictable events and reducing the severity of crashes when they do take place.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Highway engineering in rural environments traditionally stresses the importance of clear zones on either side of a roadway to provide long sight lines and leeway for driver error and recovery (Figure 1a) (1). In contrast, recent studies in urban settings suggest that human-scale streetscapes, which are smaller and more narrowly enclosed by buildings and trees, may reduce crash risk by narrowing drivers' fields of view and encouraging slower, less risky driving behavior (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Enclosure is the collective effect of large objects surrounding a street, chiefly buildings and trees, to define the spatial extents of a streetscape and restrict long sight lines; it is what some urban designers say makes a street feel like an "outdoor room" (Figure 1b) (12).…”
mentioning
confidence: 94%
“…Older drivers were most often associated with low mileage. Dumbaugh and Zhang [16] investigated the causality between urban form and crashes involving senior drivers and found that community design features, such as arterial thoroughfares, commercial strips, and big box stores, were related to crashes for older adults, and that pedestrian-scaled retail areas ensured mobility for older adults. groups.…”
Section: Introductionmentioning
confidence: 99%